Declines in muscle protein synthesis account for short‐term muscle disuse atrophy in humans in the absence of increased muscle protein breakdown. Issue 4 (23rd May 2022) - Brook, Matthew S.; Stokes, Tanner; Gorissen, Stefan H.M.; Bass, Joseph J.; McGlory, Chris; Cegielski, Jessica; Wilkinson, Daniel J.; Phillips, Bethan E.; Smith, Ken; Phillips, Stuart M.; Atherton, Philip J.
Abstract: Background: We determined the short‐term (i.e. 4 days) impacts of disuse atrophy in relation to muscle protein turnover [acute fasted‐fed muscle protein synthesis (MPS)/muscle protein breakdown (MPB) and integrated MPS/estimated MPB]. Methods: Healthy men ( N = 9, 22 ± 2 years, body mass index 24 ± 3 kg m −2 ) underwent 4 day unilateral leg immobilization. Vastus lateralis (VL) muscle thickness (MT) and extensor strength and thigh lean mass (TLM) were measured. Bilateral VL muscle biopsies were collected on Day 4 at t = −120, 0, 90, and 180 min to determine integrated MPS, estimated MPB, acute fasted‐fed MPS (l ‐[ring‐ 13 C6 ]‐phe), and acute fasted tracer decay rate representative of MPB (l ‐[ 15 N]‐phe and l ‐[ 2 H8 ]‐phe). Protein turnover cell signalling was measured by immunoblotting. Results: Immobilization decreased TLM [pre: 7477 ± 1196 g, post: 7352 ± 1209 g ( P < 0.01)], MT [pre: 2.67 ± 0.50 cm, post: 2.55 ± 0.51 cm ( P < 0.05)], and strength [pre: 260 ± 43 N m, post: 229 ± 37 N m ( P < 0.05)] with no change in control legs. Integrated MPS decreased in immob vs. control legs [control: 1.55 ± 0.21% day −1, immob: 1.29 ± 0.17% day −1 ( P < 0.01)], while tracer decay rate (i.e. MPB) (control: 0.02 ± 0.006, immob: 0.015 ± 0.015) and fractional breakdown rate (FBR) remained unchanged [control: 1.44 ± 0.51% day −1, immob: 1.73 ± 0.35% day −1 ( P = 0.21)]. Changes in MT correlated with those in MPS but not FBR. MPS increased in the control leg following feeding [fasted: 0.043 ± 0.012% h −1, fed: 0.065 ± 0.017% h −1 ( P < 0.05)] but not in immob [fasted: 0.034 ± 0.014% h −1, fed: 0.049 ± 0.023% h −1 ( P = 0.09)]. There were no changes in markers of MPB with immob ( P > 0.05). Conclusions: Human skeletal muscle disuse atrophy is driven by declines in MPS, not increases in MPB. Pro‐anabolic therapies to mitigate disuse atrophy would likely be more effective than therapies aimed at attenuating protein degradation.